Pengaruh Event Perubahan Harga BBM terhadap Return Saham Perusahaan Manufaktur Sektor Otomotif - Maruf, Afif (Universitas Darwan Ali, 2023)
This study analyzes the effect of Announcements of Changes in Fuel Prices on Stock Returns of Manufacturing Companies in the Automotive Sub Sector Registered in Indonesia. This study uses the independent variable (X) the fuel price change event, and the dependent variable (Y) the return on manufacturing stocks in the automotive sub-sector. The sampling technique uses purposive sampling which consists of 13 companies that have been listed on the Indonesia Stock Exchange for 259 days. Data sourced from Bank Indonesia and Yahoo Finance websites. The results of this study indicate that the announcement of changes in fuel prices has no effect on the returns of manufacturing companies in the automotive sub-sector that are listed on the IDX.